indonesia - DWIANA, ANGGITA CUCU (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2024)
Abstract Literature is an essay, findings from the ideas of the human mind and forms of human culture. Wattpad is an application that contains a story that is poured on internet media which is used by the author to produce a story. Character traits are the values ??that make up a character, and often depend on one's own life circumstances. The purpose of this study is to analyze and describe how the character values ??of the main character in Wattpad Memories by Sirhayani are. The method used in this study is a qualitative method, with content analysis techniques. The data was obtained by observing and note-taking techniques, the reading technique was carried out while reading Wattpad Memories by Sirhayani which consists of 29 chapters, 994 thousand votes and has been read 15.8 million times. Based on the results of the research and discussion, the findings are as follows: 1) Integrity with 7 findings, 2) Nationalist with 9 findings, 3) Religious with 6 findings, 4) Independence with 2 findings, 5) Mutual Cooperation with 1 finding. keywords: literature, wattpad, character value